2022
DOI: 10.1016/j.jhazmat.2021.126799
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol transmission of SARS-CoV-2 due to the chimney effect in two high-rise housing drainage stacks

Abstract: Stack aerosols are generated within vertical building drainage stacks during the discharge of wastewater containing feces and exhaled mucus from toilets and washbasins. Fifteen stack aerosol-related outbreaks of coronavirus disease 2019 (COVID-19) in high-rise buildings have been observed in Hong Kong and Guangzhou. Currently, we investigated two such outbreaks of COVID-19 in Hong Kong, identified the probable role of chimney effect-induced airflow in a building drainage system in the spread of severe acute re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 49 publications
1
32
0
2
Order By: Relevance
“…The vertical outbreak came into the spotlight as a serious SARS (Severe Acute Respiratory Syndrome) outbreak happened back in 2003 at a private residential apartment in Hong Kong, resulting in 42 deaths and 321 infected cases [ 34 ]. For the current COVID-19 pandemic, 15 vertical outbreaks in residential buildings were reported in Hong Kong and Guangzhou, China [ 35 , 36 ], and one outbreak in Seoul, South Korea [ 37 ] ( Table 1 ). The infected cases were detected along the vertical line in the buildings connected by the same plumbing pipe.…”
Section: Vertical Outbreaks Of Covid-19mentioning
confidence: 99%
“…The vertical outbreak came into the spotlight as a serious SARS (Severe Acute Respiratory Syndrome) outbreak happened back in 2003 at a private residential apartment in Hong Kong, resulting in 42 deaths and 321 infected cases [ 34 ]. For the current COVID-19 pandemic, 15 vertical outbreaks in residential buildings were reported in Hong Kong and Guangzhou, China [ 35 , 36 ], and one outbreak in Seoul, South Korea [ 37 ] ( Table 1 ). The infected cases were detected along the vertical line in the buildings connected by the same plumbing pipe.…”
Section: Vertical Outbreaks Of Covid-19mentioning
confidence: 99%
“…Six publications in this review confirmed that viral aerosols in Amoy Gardens' building plumbing were sucked into unit bathrooms through floor drains, contributing significantly to the outbreak, with case studies [ 110 , 113 ], experimental studies [ 107 ], and simulations [ 108 , 111 , 112 ]. Unsurprisingly, another study cluster emerged during the Covid-19 pandemic, employing similar research approaches, such as case studies [ 117 ], experiments [ 115 , 116 ], and modelling [ 109 , 114 , 118 ]. However, the settings of SARS drainage studies were all high-rise Multi-Unit Residential Buildings (MURB), while Covid-19 studies extended the research on hospitals and general high-rise buildings.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the drainage system intervention's primary objective was to operate and maintain the existing drainage facilities properly: (1) Regular inspection: FM team is recommended to regularly inspect or deploy a defective trap identification system [ 108 ] to monitor water seal [ 114 ], such as sanitary fixtures equipped with U-traps [ 113 ]. Moreover, it is critical to control tenant installations of equipment that might cause drain lines to get clogged, resulting in pipeline congestion [ 115 ]. (2) Repair and maintenance: The case study by Wong et al highlighted the challenge of maintaining sewage systems in hospitals during the Covid-19 pandemic and the importance of accurately mapping the sewage pipework, especially in older architectures, for rapid response to pipe leakage [ 117 ].…”
Section: Discussionmentioning
confidence: 99%
“…In an outbreak of COVID-19 in vertically aligned flats in a high-rise building, Kang et al used ethane tracer gas in the bathroom for airflow and dispersion tests and clarified the importance of U-shaped water traps and bathroom ventilation [3]. In two housing blocks in Hong Kong, Wang et al used SF6 tracer gas to conduct toilet simulation experiments and believed that SARS-CoV-2 could be transmitted by long-range aerosol through drainage pipes [19]. Li et al adopted computational fluid dynamics to model the trajectories of aerosol particles during toilet flushing and observed massive upward transport of virus particles [13].…”
Section: Influence Factors Of Aerosol Transmissionmentioning
confidence: 99%
“…During quarantine, the early quarantined persons on the fifth floor and the late quarantined person in the non-vertically adjacent room on the seventh floor were detected as successively positive for the novel coronal nucleic acid. The index cases and infected case at a different layer had no direct contact before and after entering the hotel and were not the close contacts of the same confirmed case of coronavirus disease 2019 (COVID- 19), but the virus gene sequencing results were highly consistent. After investigation, there were no external windows of the rooms they lived in, the air conditioning system of the rooms was a fan coil unit and the central air conditioning air supply system to supply air partly taken from the outdoor and partly from the corridor, the sewage and drainage pipes in bathrooms of the fifth to eighth floor for quarantine did not directly exhaust from the top through the vertical pipes but were gathered to a horizontal pipe at the top of the eighth floor and then exhausted through the roof exhaust fan, which was always closed due to elevator maintenance during the quarantine period.…”
Section: Introductionmentioning
confidence: 96%